2014
DOI: 10.3201/eid2002.131094
|View full text |Cite
|
Sign up to set email alerts
|

Human Antibody Responses to Avian Influenza A(H7N9) Virus, 2013

Abstract: Understanding host antibody response is crucial for predicting disease severity and for vaccine development. We investigated antibody responses against influenza A(H7N9) virus in 48 serum samples from 21 patients, including paired samples from 15 patients. IgG against subtype H7 and neutralizing antibodies (NAbs) were not detected in acute-phase samples, but ELISA geometric mean titers increased in convalescent-phase samples; NAb titers were 20–80 (geometric mean titer 40). Avidity to IgG against subtype H7 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 35 publications
6
44
0
Order By: Relevance
“…Among samples with elevated HI titers, we observed relatively lower corresponding MN titers. This was consistent with previous experience in which the neutralizing antibody response among confirmed influenza A(H7N9) cases was relatively weak compared with the neutralizing antibody response against the 2009 pandemic A(H1N1) and avian influenza A(H5N1) virus using a similar MN assay21.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among samples with elevated HI titers, we observed relatively lower corresponding MN titers. This was consistent with previous experience in which the neutralizing antibody response among confirmed influenza A(H7N9) cases was relatively weak compared with the neutralizing antibody response against the 2009 pandemic A(H1N1) and avian influenza A(H5N1) virus using a similar MN assay21.…”
Section: Discussionsupporting
confidence: 91%
“…This may have led to a lower seroprevalence among poultry workers than we would have found had we only enrolled workers from LPMs with positive influenza A (H7N9) environmental samples. Finally, it is important to note that serologic testing may not detect all infections due to waning or lack of antibody response to influenza A(H7N9) infection, especially mild infection, and thus, our study may underestimate influenza A(H7N9) infection rates during the early stages of the outbreak15, 21.…”
Section: Discussionmentioning
confidence: 94%
“…MN titers were also lower than HI titers in patients infected with A(H7N9) virus. Guo et al (19) showed that the MN titers of A(H7N9) patients were only 20 to 80 in serum samples collected 102 to 125 days after symptom onset, compared to HI titers of 80 to 640 for the same samples (19). The MN titers after A(H7N9) infection were also much lower than those induced by A(H5N1) virus infection, in which the MN GMT in convalescent patients was 540 at 1 to 2 months after symptom onset (20).…”
Section: Discussionmentioning
confidence: 99%
“…20 The results of alternative vaccine strategies have also been subpar with both inactivated H7N9 split vaccine and H7N9 HA virus-like particle vaccine eliciting HI seroconversion rates of only 6% and 15.6% in Phase I trials respectively. 21,22 This compares poorly with the ~ 89% rate reported for similar seasonal influenza subunit vaccines. 2325 Even with the addition of adjuvant and a booster injection, the inactivated split H7N9 vaccine elicited HI seroconversion in only 59% of subjects in an early Phase II clinical trial.…”
Section: Challenges To Preparedness For An Avian H7n9 Influenza Pandemicmentioning
confidence: 57%